Long-term follow-up after pediatric hematopoietic stem cell transplantation - Pelegrina, Polliany Roberta Dorini; Gouveia , Roseane Vasconcelos; Macedo, Antonio Vaz de; Vieira, Ana Karine; Landi, Gabriela Gaspar Filgueiras; Lopes, Julia; Menezes Neto, Osvaldo Alves de; Ferreira, Rafaela de Souza; Miachon, Adriana Aparecida Siviero; Tavares , Rita de Cássia Barbosa da Silva; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
This article, part of the Pediatric Group consensus of the Brazilian Society of Bone Marrow Transplantation, addresses lifelong follow-up in pediatric hematopoietic stem cell transplant survivors. With the growing number of long-term survivors, specialized monitoring is essential, especially for high-risk groups such as infants, recipients of total body irradiation, and those with inherited bone marrow failure syndromes. The consensus outlines surveillance strategies for detecting and managing late complications, including chronic graft-versus-host disease and secondary effects. Multidisciplinary recommendations aim to optimize early intervention and quality of life, establishing a standardized follow-up framework for pediatric transplant care in Brazil.